Study on the Wettability and Spontaneous Imbibition Characteristics of Lacustrine Shale. (10th February 2022) - Xue, Haitao; Ding, Guozhi; Dong, Zhentao; Zhao, Rixin; An, Ce; Li, Boheng; Zhou, Yuan; Yan, Penglei; Yan, Jinliang; Li, Chunlei; Jin, Yuxi
Abstract : Wettability plays a significant role in the exploration and development of shale oil. The wettability affects the oil enrichment and restricts the selection of fracturing fluids. Shale is composed of complex minerals and organic matter. The pores composed of inorganic minerals have water wettability, while the pores composed of organic matter show the characteristics of oil wetting. The contact angle experiment and the spontaneous imbibition experiment are the most commonly used methods for characterizing wettability. The Qingshankou Formation in the Songliao Basin has thick source rocks, which is a favorable interval for shale oil exploration and development. Strengthening the wettability research in this area is of great significance for the exploration of shale oil. The wettability of different lithofacies shale in the northern Songliao Basin is seldom characterized, and there is a lack of comparative studies on contact angle and imbibition characteristics. In view of this situation, the shale of the Qingshankou Formation in the northern Songliao Basin has been classified. This article used the method of spontaneous imbibition combined with nuclear magnetic resonance to characterize the wettability of shale and analyze the influencing factors of the wettability of different shale lithofacies. Six samples with different lithological characteristics were used for this experiment. The study found that the imbibition results of samples with different lithofacies are different. The imbibition of sandy interlayer is less affected by the direction, while the imbibition of shale is more affected by the direction. The water imbibition volume of the sample is related to the content of clay minerals. The relationship of water imbibition volume in different lithofacies samples is as follows: low organic matter laminated siliceous shale > high organic matter massive clay shale > sandy interlayer > high organic matter laminated siliceous shale > high organic matter massive siliceous shale. Excessive content of clay minerals will cause shale to absorb water and expand and block pores, which is not conducive to further water imbibition by shale. The volume of oil imbibed is related to the organic carbon content. The relationship of oil imbibition volume in different lithofacies samples is as follows: high organic matter massive clay shale > high organic matter laminated siliceous shale > sandy interlayer > low organic matter laminated siliceous shale > high organic matter massive siliceous shale. The higher the total organic carbon content, the more developed the lipophilic pore network, and the more the volume of oil imbibed by the sample.